Gambaran Kepuasan Masyarakat Terhadap Pelayanan Di Puskesmas: Studi Kualitatif - Hamida Ansar; Hasriani (Yayasan Ekselensi Daya Indonesia, 2025)
Community satisfaction is an important indicator of primary care quality and serves as strategic input for continuous improvement at Community Health Centers (Puskesmas). This study aims to describe community satisfaction with services at the MM Community Health Center and the factors influencing it, based on qualitative findings from in-depth interviews. This study used a qualitative design with semi-structured interviews with 20 informants (patients/families) selected purposively. Data analysis used a Reflexive Thematic Analysis approach. Data validity was maintained through source triangulation, audit trails, and member checking. Five main themes influenced satisfaction: access and waiting time, communication and empathy from health workers, availability of drugs and facilities, ease of administration, and cleanliness of the facility. Informant quotes showed a variety of experiences, from very satisfied to needing improvements in the queuing system and drug availability. Improvements in service flow, strengthening communication, and monitoring of the IKM based on real-time feedback are recommended. The services at the MM Community Health Center were considered quite satisfactory, but improvements in access and drug availability are still needed